2014
DOI: 10.5604/17322693.1132010
|View full text |Cite
|
Sign up to set email alerts
|

The correlations between aging of the human body, oxidative stress and reduced efficiency of repair systems

Abstract: The article presents an current knowledge overview about the importance of oxidative stress and reduced efficiency of repair processes during the aging process of the human body. Oxidative damage to cellular macromolecules (proteins, lipids, nucleic acids), are formed under the influence of reactive oxygen species (ROS). They are the part of important mechanism which is responsible for the process of aging and the development of many diseases. The most important effects result from DNA damage, due to the mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Oxidative stress (OxS) might intensify bone resorption, underlying development of PMO. In addition, the majority of studies reported OxS is strongly linked to a variety of pathologies like infections, autoimmune diseases and others, specific to old age: cancer, neurodegenerative and CVD [51][52][53]. As OxS is also a risk factor of arteriosclerosis and cardiovascular event, it seems to be an interesting link between low bone quantity/quality, on one hand, and arteriosclerosis, on the other hand [49,50].…”
Section: Role Of Lack Of Estrogensmentioning
confidence: 94%
See 1 more Smart Citation
“…Oxidative stress (OxS) might intensify bone resorption, underlying development of PMO. In addition, the majority of studies reported OxS is strongly linked to a variety of pathologies like infections, autoimmune diseases and others, specific to old age: cancer, neurodegenerative and CVD [51][52][53]. As OxS is also a risk factor of arteriosclerosis and cardiovascular event, it seems to be an interesting link between low bone quantity/quality, on one hand, and arteriosclerosis, on the other hand [49,50].…”
Section: Role Of Lack Of Estrogensmentioning
confidence: 94%
“…Hcy can increase osteoclastic activity, decrease osteoblastic function and bind directly to bone extracellular matrix, reducing bone strength. Hyperhomocysteinemia (HHcy) may produce also some mitochondrial abnormalities, which can alter bone properties through generations of ROS [50,51]. However, the mechanism of HHcyinduced bone loss via the mitochondrial pathway is largely unknown.…”
Section: Role Of Lack Of Estrogensmentioning
confidence: 99%
“…Among the best recognized chemical agents which are attributable to the generation of oxidative stress, are indicated heavy metals, air pollution, plant protection products and tobacco smoke [4,5,6,7]. The physical factors responsible for inducing this phenomenon are electromagnetic fields [8] and ionizing radiation (IR) [9].…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Health behaviours, including nutritional [10], play an important role in the generation of oxidative stress and combatting its effects [3]. An intensification of oxidative stress and reduced efficiency of the cell-repairing mechanisms are associated with the process of ageing of the body [7]. Considering the simultaneous effect of the above-mentioned factors on the human body, it is difficult to isolate and determine the strength of the effect of individual factors on human reproductive health.…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Well-functioning repair systems remove damage and prevent harmful changes in cells. Unfortunately, with age, they are weakened, which contributes to an increase in the number of damaged cells[5].Changes related to the aging of the body and increasingly becoming associated with the operation of ROS. In order to avoid the accumulation of ROS, the body has developed mechanisms of antioxidant defense, which include, among others, the action of enzymes such as CAT, SOD, GST, GPx, or nonenzymatic antioxidants such as GSH.…”
mentioning
confidence: 99%